Application of wound dressings based on bacterial cellulose in the healing of chronic and complex wounds: Trends and perspectives (Research, Society and Development, 2024)
The aim of this study was to carry out a narrative literature review of the most recent studies and technological advances related to the biomedical applications of dressings composed of bacterial cellulose biopolymer (BC) in the healing of chronic and complex wounds. BC can be produced on a large scale through a fermentation process by specific bacteria. Cellulose fibrils form a highly porous network, similar to the structure of the extracellular matrix of tissues, as well as having favorable physicochemical characteristics for applications as dressings. Recent studies have shown the importance of and interest in incorporating active pharmaceutical ingredients of both synthetic and natural origin, with the aim of conferring specific pharmacological properties to the structure of these polymeric matrices. The physicochemical versatility of BC allows this material to be functionalized and modified through various techniques, both ex situ and in situ, to obtain new hybrid materials with functional properties for different biomedical applications. Among the pharmaceutical active ingredients incorporated into a CB matrix for application to chronic and complex wounds are antiseptic and antimicrobial active ingredients, anti-inflammatories from natural sources and growth factors. Another strategy that has proved promising is the application of mesenchymal stem cells and components of their secretome in the polymeric matrix of the BS. Therefore, this review sheds light on the latest technological advances regarding the different ways of functionalizing BC-based dressings for the treatment of chronic and complex wounds.